Hệ thống khảo thí trực tuyến trên mạng - Vu, Thanh Nguyên (Journal of Technical Education Science, 2007)
Many methods are used for checking and evaluating results of traning and learning process today. One from those methods is objective test method used to evaluate re- sults of education and training widely. This article overviews all methods for checking and evaluating results of training and learning process as writing test method, practice test method, oral test method…based on this methodology, the author set up online exam system using objective test. This system has been used in many universities in HoChiMinh City